(untitled) (World Bulletin of Public Health, 2023)
The article emphasizes the use of international experience in the development of tourism in agriculture, and the methodological basis of the study was formed as a result of the study of theoretical and practical data, scientific sources and publications. The research is based on connections between theory and practice and uses methods such as analysis, comparison, analogy and synthesis.